Best Bricks: a study of advertised brick pricing in Victorian New Zealand - Divehall, Dean; Isaacs, Nigel (Architectural History Aotearoa, 2013)
While timber was suitable for construction, more than permanent materials were needed for real buildings. Stone was available but transport limited its distribution. Bricks could be made almost anywhere. This paper examines New Zealand brick pricing based on advertised data from published newspapers across the Wellington, Nelson, Canterbury, Otago and Auckland regions. It provides an overview of brick pricing during this critical period of the birth of colonial New Zealand. The price of bricks will be compared with other essential supplies, to help understand changes in the cost of buildings.